Mengukur Kinerja Juru Parkir Di Asahan Dengan Bantuan Machine Learning Method K-Nearest Neighbor - Ningsih, Septia; Nasution, Akmal; Santoso (STMIK Royal Kisaran, 2025)
Abstract: Information Technology (IT) has played a crucial role in various sectors, including the transportation sector, as seen in the Department of Transportation of Asahan Regency, North Sumatra. One of the challenges in this area is the performance of parking attendants, which affects the effectiveness of parking management and traffic safety. Poor performance of parking attendants can cause various issues, including traffic congestion, rule violations, and user discomfort. Therefore, evaluating the performance of parking attendants is essential to improve service quality and parking safety. In this context, the implementation of a technology-based information system is an appropriate solution to enhance the effectiveness of the performance evaluation process for parking attendants. Classification methods, such as k-nearest neighbor (KNN), are used to evaluate the performance of parking attendants more accurately and efficiently. This method allows early detection of poor performance, such as fraud or traffic rule violations, and provides feedback for improvements. The primary goal is to measure effectiveness, identify areas for improvement, and recognize parking attendants with good performance. Keywords: Information Technology, Parking Attendants, Performance Evaluation, KNN, Asahan Regency. Abstrak: Teknologi Informasi (TI) telah memainkan peran penting dalam berbagai sektor, termasuk sektor transportasi, seperti yang terlihat pada Dinas Perhubungan Kabupaten Asahan, Sumatera Utara. Salah satu tantangan di wilayah ini adalah kinerja juru parkir yang mempengaruhi efektivitas pengelolaan parkir dan keselamatan lalu lintas. Kinerja juru parkir yang kurang optimal dapat menimbulkan berbagai masalah, termasuk kemacetan, pelanggaran aturan, dan ketidaknyamanan pengguna parkir. Oleh karena itu, penilaian kinerja juru parkir menjadi sangat penting untuk meningkatkan kualitas layanan dan keamanan parkir. Dalam konteks ini, penerapan sistem informasi berbasis teknologi menjadi solusi yang tepat untuk meningkatkan efektivitas proses penilaian kinerja juru parkir. Metode klasifikasi, seperti k-nearest neighbor (KNN), digunakan untuk mengevaluasi kinerja juru parkir dengan lebih akurat dan efisien. Metode ini memungkinkan deteksi dini terhadap kinerja buruk, seperti penipuan atau pelanggaran aturan lalu lintas, serta memberikan umpan balik untuk perbaikan. Tujuan utamanya adalah mengukur efektivitas, mengidentifikasi area perbaikan, dan memberikan apresiasi bagi juru parkir yang memiliki kinerja baik. Kata Kunci: Teknologi Informasi, Juru Parkir, Penilaian Kinerja, KNN, Kabupaten Asahan.